Inflation Targeting in Uzbekistan: Background and First Results - Shukhratovna, Yakubova Shamshinur (Research Parks Publishers, 2023)
This article describes the measures taken to introduce a new regime for the implementation of monetary policy in Uzbekistan and the economic results achieved. Specific and adequate scientific proposals and recommendations for the further implementation of inflation targeting (IT) are given.